2017
DOI: 10.3233/jad-161215
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiles in Diabetes and Dementia

Abstract: Lipids are a diverse class of hydrophobic and amphiphilic molecules which make up the bulk of most biological systems and are essential for human life. The role of lipids in health and disease has been recognized for many decades, as evidenced by the early identification of cholesterol as an important risk factor of heart disease and the development and introduction of statins as a one of the most successful therapeutic interventions to date. While several studies have demonstrated an increased risk of dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 108 publications
1
25
0
Order By: Relevance
“…Similarly to LP, we also found that PC-PLs were inversely related to T2D risk. Plasmalogens have been widely investigated because of their role as endogenous antioxidants, limiting the oxidation of other lipids (7,22). They may also decrease the risk of T2D through other beneficial mechanisms, such as antiapoptotic and anti-inflammatory functions (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to LP, we also found that PC-PLs were inversely related to T2D risk. Plasmalogens have been widely investigated because of their role as endogenous antioxidants, limiting the oxidation of other lipids (7,22). They may also decrease the risk of T2D through other beneficial mechanisms, such as antiapoptotic and anti-inflammatory functions (7).…”
Section: Discussionmentioning
confidence: 99%
“…molecular lipid species play in T2D development remains unclear. Hypercaloric and low-quality diets also contribute to T2D by leading to an excess of fat depositions, which is enhanced by insulin resistance, resulting in lipotoxicity (7). Lipidomics may help to clarify the biological mechanisms underlying the link between dyslipidemia, nutrition, and T2D.…”
mentioning
confidence: 99%
“…Thus, a large number of human pathologies are linked to alterations of lipid homeostasis including in addition to a number of genetic disorders (Hobbs et al, 1992), common diseases such as obesity and diabetes (Huynh et al, 2017), cardiovascular disease (Kolovou et al, 2015), cancer (Yang and Han, 2016), and neurodegenerative disease (Naudí et al, 2015; Huynh et al, 2017), among others.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] This high-throughput method and process enable us to obtain the metabolism information by means of quantifying changes in individual lipid species that reect metabolic differences, even provides favorable conditions for the diagnosis of diseases. 15,16 Studies have shown that more and more diseases are associated with lipid metabolism disorders, such as hypertension, 17 kidney diseases, 18 diabetes, 19,20 hepatopathy, 21 and other diseases.…”
Section: Introductionmentioning
confidence: 99%